English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Ok, that makes sense, but then why does x^2+5x+6=0 equal (x+2)(x+3)=0

2006-10-30 16:01:12 · 5 answers · asked by p_rob22 1 in Science & Mathematics Mathematics

5 answers

(x + 2)(x + 3)=0
x(x + 3) + 2(x + 3) = 0
x^2 + 3x + 2x + 6 =0
x^2 + (3x + 2x) + 6 =0
x^2 + 5x + 6 = 0

or
(x + 3)(x + 2)=0
x(x + 2) + 3(x + 2) = 0
x^2 + 2x + 3x + 6 =0
x^2 + (2x + 3x) + 6 =0
x^2 + 5x + 6 = 0

proofed

How to make x^2+5x+6=0 became (x+2)(x+3)=0

1. x^2+5x+6=0
2. Because first is power of 2 its mean create (x + ?)(x + ?) = 0
3. First parameter let say a and second is b
4. (x + a)(x + b) = 0
5. Think about a+b=5 & a*b =6
6. Finish? yes you right a=2 and b=3 or if a=3 then b=2

2006-10-30 16:37:58 · answer #1 · answered by safrodin 3 · 0 0

Factor means to undo some multiplication.

(x + 2) (x + 3) becomes x² + 5x + 6 because

when you multiply (x + 2) (x + 3), you get x² + 5x + 6.

FOIL is an acronym that helps you organize the distributive property. Really want you need to do is take ...

x (x + 3) + 2 (x + 3) ... distribute both expressions and combine terms where you can.

x (x + 3) = x² + 3x.

Now you try to other and combine terms!

Good Luck!

2006-10-31 00:10:57 · answer #2 · answered by TripleFull 3 · 0 0

x^2+5x+6=0
(x+2)(x+3)
multiply the binomials using FOIL
First: x*x=x^2
Outside: x*3=3x
Inside: 2*x=2x
Last: 2*3=6
add like terms
x^2+(2+3)x+6=x^2+5x+6 right where you started.

2006-10-31 00:56:12 · answer #3 · answered by yupchagee 7 · 0 0

you must ask yourself...what 2 numbers will add to give me 5 (for the 5x) and multiply together to give me 6
so 2+3=5 and 2 x 3=6 so those are the numbers that you substitute in for the 5x
now we have
x^2+3x+2x+6=0
(x^2+3x)+(2x+6)=0 now we take out the greatest common factor
x(x+3)+2(x+3) now we put down the pair once and we put down the x+2 so...
(x+2)(x+3)=0
x+2=0 then x= -2
x+3=0 then x= -3

one more
x^2+7x+10...what two numbers multiply to give us 10 and add to give us 7
find those numbers and substitute them in for 7x and then finish it out

did you end up with

x= -2 and x= -5

if so you win!!!

2006-10-31 02:37:55 · answer #4 · answered by ineedonebuddy 3 · 0 0

Multiply it yourself, using FOIL. Do you know the FOIL method, first, outer, inner, last?

You multiply the "first" term in each factor, x * x = x^2
Then you multiply the "outer" term in each factor, x * 3 = 3x
Then you multiply the "inner" term in each factor, 2 * x = 2x
Then you multiply the "last" term in each factor, 2 * 3 = 6

Then you add 'em all up and get x^2 + 5x + 6

2006-10-31 00:06:17 · answer #5 · answered by ? 6 · 0 0

fedest.com, questions and answers